Clinical value of stress transaortic flow rate during dobutamine echocardiography in low-gradient aortic stenosis. (8th February 2021) - Vamvakidou, A; Pibarot, P; Plonska-Gosciniak, E; Almeida, AG; Kukulski, T; Kasprzak, JD; Flachskamf, F; Senior, R
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND/INTRODUCTION The clinical value of rest transaortic flow rate (FR) has been shown previously in low-gradient aortic stenosis (LGAS) for the prediction of outcome. However limited data exists on the prognostic value of stress FR in LGAS following low-dose dobutamine stress echocardiography (LDDSE). PURPOSE: We aimed to assess the value of stress FR in patients with LGAS in the diagnosis of AS severity and the prediction of mortality. METHODS: This is a multi-centre cohort study of patients with low left ventricular ejection fraction (LVEF) and LGAS (aortic valve area –AVA <1cm²) who underwent LDDSE. RESULTS: Of the 287 patients (mean age:  75.1 ±10 years, males: 71%) over the mean follow-up of 24 ±30 months there were 127 (44.3%) deaths and 147 (51.2%) patients underwent aortic valve intervention. Lower stress FR was independently associated with increased risk of mortality (HR= 0.99, 95%CI= 0.99-0.999, p= 0.02) after adjusting for age, chronic kidney disease, presence of symptoms (NYHA II-IV), aortic valve intervention, rest LVEF and guideline-defined severe AS (AV mean gradient- AVMG ≥40mmHg with AVA <1cm² at peak stress).  The minimum cut-off for prediction of mortality was stress FR 210ml/sec. Among the different criteria of AS severity during stress, i.e. guideline-defined criterion, or stress AVMG ≥40mmHg, or stress AVA <1cm² at stress FR ≥210ml/s, only the latter was independently associated with mortality (HR= 1.81, 95%CI= 1.04-3.2, p= 0.04) (Table 1) and was the parameter of AS severity that predicted improved outcome following aortic valve intervention (p <0.005) (Figure 1). Guideline-defined stroke volume flow reserve did not predict mortality. CONCLUSIONS: Assessment of stress FR during LDDSE is important for the detection of both AS severity and flow reserve.